2019
DOI: 10.1021/acsmedchemlett.9b00063
|View full text |Cite
|
Sign up to set email alerts
|

Do Zebrafish Obey Lipinski Rules?

Abstract: The use of zebrafish in whole organism phenotypic assays has become a valuable strategy throughout the drug discovery process. Zebrafish assays can be used not only to screen libraries of compounds at the earliest stages but also to evaluate advanced leads for their effects on specific biological pathways or for toxicity. However, when confronted with inactivity of a compound in a zebrafish assay, there are little data that can be used to judge if the compound is truly biologically inert or inactive due to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
3
25
1
Order By: Relevance
“…We the PK parameters. These findings align with studies on the absorption of compounds in zebrafish eleuthero-embryo [ [19][20][21] ] that have found that the higher the lipophilicity, the higher the uptake.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We the PK parameters. These findings align with studies on the absorption of compounds in zebrafish eleuthero-embryo [ [19][20][21] ] that have found that the higher the lipophilicity, the higher the uptake.…”
Section: Discussionsupporting
confidence: 89%
“…Among other molecular descriptors, i.e., polar surface area (TPSA), molar refractivity (MR), number of H-bond acceptors (HBA), H-bond donors (HBD) and rotatable bonds (rotor), the QSPkR analysis identified LogD as the most important physicochemical descriptor to explain the PK parameters. These findings align with studies on the absorption of compounds in zebrafish eleuthero-embryo [ [19][20][21] ] that have found that the higher the lipophilicity, the higher the uptake.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The absorptive ability of zebrafish eleuthero-embryos and larvae is largely determined by the physicochemical properties of the compounds. Studies have shown that among a wider number of molecular descriptors, lipophilicity plays the largest role in absorption 19 21 . Although somewhat more time-consuming, a way to circumvent a possible relative lack of absorption, is to microinject compounds into the animals.…”
Section: Introductionmentioning
confidence: 99%